(3oZQQ GdMce hoOQQ Gdcdes - (3CHhGdaJM fGUM GdOjf YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdJejej GdBeOjs; (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s ((3CMeO Hf eMeO GdMSjfj CMeO s)
(3ChdgG (B:s
(3hHYO aEf GdPj MOGfj Ydi JNUjUg ahGFO gPG GdcJGH s
(3BNQgG (B:s
(3jbHM HGdQLd Cf jbUQ Yedg Yf Ydeg, hjYLR aYdg Yf bhdg s
(3hJJab aj ChdgG hBNQgG eY GdfSNI GdChdi eY GNJdGa aj HYV GdCdaGXs
(3ef cdGe Ydj Hf CHj WGdH GdeJhai (B40 (3g`s
(3fSNI KGdKI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdCOHs